Práticas de governança corporativa adotadas e divulgadas pelos fundos de pensão brasileiros - Lima, Leticia Cesar de (2014)
Pension funds move a great amount of resources on behalf of third parties, which involve millions of workers, and, therefore, it is considered that such entities should adopt high standards of governance in order to have credibility for all those involved. Good governance practices contribute to more harmony among interests by those involved and for the proper functioning of pension funds. Corporate governance consists of a system by means of which entities are administrated, monitored and supported, while safeguarding all interested parties such as owners, administration councils, directors and controlling organs. Institutional theory offers multiple perceptions belonging to the investigation of institutional pressures and subsequent organizational actions, which, when exposed to similar conjunctures, tend to resemble each other, which leads to institutional isomorphism. Such isomorphism might be classified as coercive, when it originates from formal or informal outer pressure; mimetic, when organizations take others as role models, due to uncertainty; or normative, when it is caused by social or professional pressure. Considering the fragility in the Brazilian regulation concerning governance practices in pension funds, in the coercive isomorphism vision, this study is based on the hypothesis that the disclosure of corporate governance practices adopted by Brazilian pension funds presents blanks, and most practices disclosed are due to coercive institutional pressure. Thus, this research aims at analyzing corporate governance practices adopted by Brazilian pension funds and likely explanations by the light of Institutional Theory. In order to do that, documental analysis was used, and the internet portals of studied pension funds provided the documents. Then, there was the analysis of content in the material obtained. As a consequence, descriptive statistics was applied in order to assess, based on isomorphism, governance practices by pensions. Subsequently, there was the verification of fund associations based on governance practices and categories by means of cluster analysis in a search for isomorphic behavior. The result obtained was that Brazilian pension funds tend to adopt and disclose predominantly the governance practices which are legally imposed, which leads to coercive isomorphism. It is also observed that age, and size of funds in terms of assets and sponsorship are variables which are related to voluntary practices, which will also lead to mimetic isomorphism.